Breaking the silicon ceiling: Gender equality and information technology in Pakistan. (4th May 2018) - Tanwir, Maryam; Khemka, Nitya
Abstract: In a rapidly globalizing world, high growth sectors like information technology (IT) hold the key to narrow or broaden the gulf between men and women at work. However, there is a serious underrepresentation of women in the technology sector, particularly in leadership roles. This gulf between men and women at work is likely to widen unless immediate action is taken. ICT jobs can provide women with greater opportunities and higher wages, compared to the low-skill jobs that women are often crowded into. Yet, achieving gender neutrality and inclusivity in the IT sector is an uphill task. This paper focuses on the challenges, opportunities and conditions that can be created to facilitate the participation of urban, educated women of Pakistan in the IT sector. Although the empowerment aspects of individualization in the workplace for women are tangible, in Pakistan, there are a number of socio-cultural barriers and an implicit gender bias in education and employment which prevents greater participation of women in the IT sector. The paper also sets out specific recommendations for the government and private sectors to further increase gender inclusivity in employment. In doing so, it draws upon primary research and current behavioral economic insights and makes the case that a multi-sectoral effort involving the private sector, government, and macro-social environment is critical to radically disrupting bias, providing norm-changing solutions, and ensuring rapid gains to the economy from the inclusion of women in the sector.